Neural correlates of appreciating natural landscape and landscape garden: Evidence from an fMRI study. Issue 7 (1st June 2019) - Zhang, Wei; He, Xianyou; Liu, Sizhe; Li, Ting; Li, Jinhui; Tang, Xiaoxiang; Lai, Shuxian
Abstract: Introduction: Rambling natural landscapes or landscape gardens may invoke positive emotions. However, the manner in which people experience landscape gardens and the cortical differences in the appreciation of the naturalness and artificiality of landscapes remain unknown. Methods: This study scanned participants with functional magnetic resonance imaging while they viewed photographs of natural landscapes and landscape gardens and performed scene type judgment task. Results: As predicted, we identified brain regions that were associated with perceptual process, cognitive process, and rewarding experience when appreciating natural landscapes and landscape gardens without color preference. Meanwhile, the contrast between the appreciation of landscape gardens and natural landscapes was characterized by stronger activations of the inferior occipital lobe, the left superior parietal lobule (SPL), the right fusiform gyrus, the right cuneus, and the right hippocampus. Conclusions: Responses in these regions indicate that the appreciation of landscape gardens and natural landscapes relies on common cortical regions, and suggest the possibility that the inferior occipital lobe, the SPL, the fusiform gyrus, and the cuneus may be specifically associated with the appreciation of landscape gardens. Abstract : The appreciation of landscape gardens and natural landscapes relies on common cortical regions, and suggest the possibility that the inferior occipital lobe, the superior parietal lobule, the fusiform gyrus, and the cuneus may be specifically associated with the appreciation of landscape gardens.